Glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode and its construction method

By using CC/AuNPs/PPy@MnO2 electrode material, the problem of low conductivity of existing EBFC electrode materials is solved, more efficient electron transfer and more stable electrode performance are achieved, and the overall performance of enzyme biofuel cells is improved.

CN118899490BActive Publication Date: 2025-02-07NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411325436.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-07
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing enzyme biofuel cells (EBFCs) have a slow electron transfer rate due to the low conductivity of the electrode materials, which limits the improvement of the electrochemical performance of EBFC.

Method used

Using CC/AuNPs/PPy@MnO2 electrode material, carbonized polypyrrole (PPy) and manganese dioxide (MnO2) composite materials are prepared through hydrothermal reaction, combining nano-gold particles (AuNPs) and carbon cloth to improve the conductivity and ratio of the electrode. Capacitor performance.

Benefits of technology

It significantly improves the open circuit voltage and power density of enzyme biofuel cells, improves the stability of the electrode and the fixed efficiency of the enzyme, and achieves more efficient electron transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118899490B_ABST
    Figure CN118899490B_ABST
Patent Text Reader

Abstract

The present invention provides a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode and a construction method thereof. The present invention uses carbon cloth CC on which nano-gold particles AuNPs are electrodeposited as a substrate, carbonized polypyrrole PPy and manganese dioxide supercapacitor composite material PPy@MnO2 as an electrode material, anode loaded with glucose oxidase (CC / AuNPs / PPy@MnO2 / GOx), cathode loaded with laccase (CC / AuNPs / PPy@MnO2 / Lac), to construct a glucose fuel cell. The PPy@MnO2 material has the characteristics of being fluffy and porous, having a large specific surface area and high specific capacitance, which is beneficial to the mass transfer of substances in the electrode liquid and the conductivity of the electrode surface, effectively enhancing the enzyme fixation efficiency and the long-term stability of the electrode, thereby comprehensively improving the overall performance and efficiency of the EBFC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of enzyme biofuel cells, in particular to a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrodes and a construction method thereof. Background Art

[0002] Enzymatic biofuel cells (EBFC) are a type of green energy conversion device that uses the catalytic action of enzymes to convert chemical energy stored in biomass fuels into electrical energy. They are environmentally friendly and pollution-free during operation, and are expected to become one of the new ways to develop renewable energy. Biofuel molecules are oxidized and converted by enzymes at the anode to produce electrons, which are transported to the cathode through an external circuit and reduced, thus completing the entire energy conversion cycle. Since the active center of the enzyme is often located in the center of the enzyme protein molecular structure, the direct transfer rate of electrons from the active center of the enzyme to the electrode (i.e., the electron acceptor) is greatly slowed down. Therefore, the low conductivity of the electrode material has become one of the key factors restricting the improvement of the electrochemical performance of EBFC.

[0003] In order to overcome this challenge, the scientific research community generally focuses on developing new materials with excellent conductivity, high specific surface area, outstanding electrochemical stability and excellent biocompatibility, and applying them to build an efficient electron transfer bridge between the enzyme active center and the electrode, aiming to significantly accelerate the electron transfer efficiency and thereby promote the overall performance of EBFC. Summary of the invention

[0004] In view of this, the present invention provides a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode and a construction method thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for constructing a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode, comprising:

[0007] 1) dispersing carbonized polypyrrole powder into a potassium permanganate solution and performing a hydrothermal reaction to obtain a PPy@MnO2 composite material;

[0008] 2) Printing circuits on flexible plastic films by screen printing, using carbon cloth electrodeposited with NaAuCl4 as the electrode working area, and applying a suspension containing PPy@MnO2 powder droplets on the electrode working area to obtain CC / AuNPs / PPy@MnO2 electrodes;

[0009] 3) dripping glucose oxidase solution on the working area of ​​the CC / AuNPs / PPy@MnO2 electrode obtained in step 2), and fixing it with chitosan solution after drying to obtain a CC / AuNPs / PPy@MnO2 / GOx electrode; dripping laccase solution on the working area of ​​the CC / AuNPs / PPy@MnO2 electrode obtained in step 2), and fixing it with Nafion solution after drying to obtain a CC / AuNPs / PPy@MnO2 / Lac electrode;

[0010] (4) Using CC / AuNPs / PPy@MnO2 / GOx electrode as the bioanode, CC / AuNPs / PPy@MnO2 / Lac electrode as the biocathode, and glucose as the fuel, a dual-chamber glucose fuel cell was constructed with the anode chamber and cathode chamber separated by a Nafion membrane.

[0011] Preferably, in step 1), the carbonized polypyrrole is prepared by a soft template method: first, a FeCl3·6H2O solution is added to a methyl orange solution, and the reaction product is used as an initiator; then, a pyrrole monomer is added under stirring, and polypyrrole is grown using the initiator as a template, followed by filtering, washing, and drying, and then the dried polypyrrole product is calcined in a tubular furnace at 800 to 1200° C. under nitrogen protection to obtain carbonized polypyrrole.

[0012] More preferably, the concentration of the FeCl3·6H2O solution is 40.0 mM to 120.0 mM, the concentration of the methyl orange solution is 4.0 mM to 8.0 mM, the volume ratio of the FeCl3·6H2O solution to the methyl orange solution is 1:1 to 1:10; and the concentration of the pyrrole monomer is 0.02 mM to 0.1 mM.

[0013] Preferably, in step 1), the concentration of the potassium permanganate solution is 1.0-8.0 mg / mL, the mass ratio of the carbonized polypyrrole to potassium permanganate (solute in the potassium permanganate solution) is 1:10-5:10; and the hydrothermal reaction is a constant temperature reaction at 80-120° C. for 4-8 hours.

[0014] Preferably, in step 2), the concentration of the NaAuCl4 solution is 2.0 to 8.0 mM; the electrodeposition is performed at a potential of -1.0 V to -0.2 V for 200 s to 400 s.

[0015] Preferably, in step 2), the concentration of the suspension containing PPy@MnO2 powder is 4.0-10.0 mg / mL.

[0016] Preferably, in step 3), the concentration of the glucose oxidase solution is 2.0-8.0 mg / mL; the concentration of the laccase solution is 2.0-8.0 mg / mL.

[0017] Preferably, in step 3), a ferrocene solution with a concentration of 0.1 M is added as an electron mediator before drop-coating the glucose oxidase solution; and an ABTS solution with a concentration of 10.0 mM is added as an electron mediator before drop-coating the laccase solution.

[0018] Preferably, in step 4), the CC / AuNPs / PPy@MnO2 / GOx electrode is immersed in PBS (0.1M, pH 7.0) buffer containing 10.0 mM glucose; the CC / AuNPs / PPy@MnO2 / Lac electrode is immersed in 0.1 M BR buffer (pH 5.0).

[0019] The present invention also provides a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode, which is obtained by any of the above construction methods.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention uses carbon cloth (CC) on which gold nanoparticles (AuNPs) are electrodeposited as a substrate, and uses a prepared carbonized polypyrrole (PPy) and manganese dioxide (MnO2) supercapacitor composite material (PPy@MnO2) as an electrode material for a glucose / O2 enzyme biofuel cell (EBFC). The advantage of the composite material is that the rough surface of the carbonized PPy is more conducive to the adsorption of the enzyme inside and outside the porous structure of the electrode surface, AuNPs improve the conductivity of the electrode, and the introduction of MnO2 significantly improves the specific capacitance of the material, effectively enhancing the enzyme fixation efficiency and the long-term stability of the electrode, thereby comprehensively improving the overall performance and efficiency of the EBFC.

[0022] The results show that the glucose / O2 enzyme biofuel cell prepared by PPy@MnO2 material has an open circuit voltage of up to 0.68V and a power density (0.35mW·cm -2 ) compared with the enzyme biofuel cell prepared from pure PPy electrode (0.21 mW·cm -2 ) increased by 66.67%. The glucose / O2 enzyme biofuel cell prepared by PPy@MnO2 material has high stability, which is mainly attributed to the porous structure and large specific surface area of ​​calcined PPy@MnO2, which provide higher enzyme loading sites, promote more efficient electron transfer between enzyme and electrode, and increase specific capacitance brought by the incorporation of MnO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1Schematic diagram of the structure, stacked electrode arrangement and electrode structure of the CC / AuNPs / PPy@MnO2 glucose fuel cell designed for the present invention, wherein: 1. cathode cell, 2. Nafion membrane, 3. cathode electrode, 4. anode cell, 5. anode electrode, 6. copper tab, 7. PPy@MnO2 / Lac enzyme layer, 8. PPy@MnO2 / GO x Enzyme layer, 9. Carbon cloth layer, 10. AuNPs coating;

[0024] Figure 2 a is a cyclic voltammetry curve (CV) of the anode electrode prepared by the present invention and the control; Figure 2 b is a cyclic voltammetry (CV) curve of the cathode electrode prepared in the present invention under different atmosphere environments;

[0025] Figure 3 This is a SEM image of the carbonized polypyrrole / manganese dioxide composite material prepared by the present invention;

[0026] Figure 4 The XPS graphs of the carbonized polypyrrole / manganese dioxide composite material prepared by the present invention and the control;

[0027] Figure 5 GCD curves of the CC / AuNPs / PPy@MnO2 / GOx electrode prepared in the present invention; (a) GCD curves of the CC / AuNPs / PPy@MnO2 / GOx electrode and the control; (b) GCD curves of the CC / AuNPs / PPy@MnO2 / GOx electrode at different current densities;

[0028] Figure 6 Polarization curve, power density curve and long-term stability experimental results of the enzyme biofuel cell operated by the CC / AuNPs / PPy@MnO2 / GOx electrode prepared in the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example

[0031] The method for constructing a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode of the present invention comprises the following steps:

[0032] 1. Preparation of Carbonized Polypyrrole Tubes

[0033] Polypyrrole (PPy) was synthesized by the soft template method. First, 80.0 mM FeCl3·6H2O and 5.0 mM methyl orange solution were prepared. The FeCl3·6H2O solution was slowly added to the methyl orange solution in a volume ratio of 1:2 under stirring to generate red flocs and then allowed to stand for 1 hour. Then, 0.05 M pyrrole monomer was slowly added under stirring and reacted at room temperature for 24 hours. The reaction product was then collected by filtration, washed with purified water and ethanol until colorless, and dried in an oven at 60°C for 24 hours. The dried PPy product was calcined in a tubular furnace at 800°C for 3 hours under nitrogen protection to obtain carbonized PPy.

[0034] 2. Preparation of Carbonized Polypyrrole and Manganese Dioxide Composites

[0035] 1.0 g of KMnO4 was added to 80.0 mL of deionized water and stirred until it was completely dissolved. Then, under ultrasonic conditions, 0.3 g of calcined carbonized polypyrrole powder was evenly dispersed therein, followed by dropwise addition of 1.0 mL of concentrated hydrochloric acid (HCl, 37%) and further stirring for 30 min. The above mixture was transferred to a 100.0 mL hydrothermal reactor and reacted at a constant temperature of 100 ° C for 6 h. After naturally cooling to room temperature, it was washed several times with purified water and anhydrous ethanol in turn. After drying in an oven at 60 ° C for 12 h, the final black fluffy powder (PPy@MnO2) was obtained, and its microscopic morphology is as follows: Figure 3 shown.

[0036] 3. Preparation of bioanode and biocathode based on PPy@MnO2 composites

[0037] First, a conductive circuit was made on a flexible plastic film by screen printing. Then, the carbon cloth was immersed in a H2SO4 solution (0.5 mol / L) containing 5.0 mM NaAuCl4. Subsequently, the carbon cloth was electrodeposited at a potential of -0.4 V for 200 s to 400 s to increase its conductivity. The treated carbon cloth was cut into a circle with a diameter of 0.5 mm and combined with a screen-printed circuit as a current collector and material loading platform. The finished product is shown in FIG. Figure 1 shown.

[0038] The carbonized PPy@MnO2 was prepared into a 10.0 mg / ml suspension, and 30 μL was loaded on the surface of the carbon cloth electrode by the drop coating method. It was naturally air-dried at room temperature, and then 20 μL of 0.1 M ferrocene solution was added as an electron mediator, and then 10 μL of 5.0 mg / mL glucose oxidase (GOx) solution was drop coated. Finally, 5 μL of 0.5% chitosan solution was drop coated on the outermost layer to prevent the loaded material from falling off. The anode electrode was obtained, which was recorded as CC / AuNPs / PPy@MnO2 / GOx.

[0039] 30.0 μL of 10.0 mg / mL PPy@MnO2 suspension was loaded on the surface of the carbon cloth electrode by drop coating method and naturally air-dried at room temperature. Then 20 μL of 10.0 mM ABTS solution was added as an electron mediator, and 10 μL of 5 mg / ml laccase (Lac) was drop coated. The outermost layer modifier was replaced with 0.5% Nafion solution to prevent the material from falling off. The cathode electrode was obtained, which was recorded as CC / AuNPs / PPy@MnO2 / Lac.

[0040] 4. Enzyme Biofuel Cell Structure

[0041] The results of the enzyme biofuel cell prepared by the present invention are as follows Figure 1 As shown, it includes an anode chamber, a cathode chamber, a diaphragm, an anode, a cathode and other components. The anode chamber and the cathode chamber are separated by a Nafion membrane 2, and the anode electrode 5 is a CC / AuNPs / PPy@MnO2 / GOx electrode immersed in a PBS (0.1M, pH 7.0) buffer containing 10.0mM glucose; the cathode electrode 3 is a CC / AuNPs / PPy@MnO2 / Lac electrode immersed in a 0.1M BR buffer (pH 5.0).

[0042] 5. Electrode performance test

[0043] The electrochemical properties of the electrode materials prepared above were characterized by a three-electrode system on a CHI660E electrochemical workstation, in which CC / AuNPs / PPy@MnO2 / GOx and CC / AuNPs / PPy@MnO2 / Lac were used as working electrodes, Ag / AgCl was used as reference electrode in 3M KCl, and foil (1 cm 2 ) was used as the counter electrode, and all tests were carried out at room temperature.

[0044] The oxidation performance of CC / AuNPs / PPy@MnO2 / GOx electrode for glucose was tested. The electrolyte was 0.1 M PBS buffer (pH 7.0). The test method was cyclic voltammetry (CV) with a scanning range of -0.2 V to 0.6 V (vs. Ag / AgCl) and a scanning rate of 10 mV·s -1 .

[0045] Test results such as Figure 2 As shown in a, the electrochemical response of the electrode prepared with PPy@MnO2 is better than that of the blank electrode and the electrode prepared with pure PPy.

[0046] The capacitive performance of CC / AuNPs / PPy@MnO2 electrode was tested. The electrolyte was a 0.5M NaSO4 solution. The test method was a constant current charge and discharge test (GCD) with a voltage range of -0.3V to 0.8V (vs. Ag / AgCl).

[0047] Test results such as Figure 5 a and Figure 5 As shown in b, at the same current density (1Ag -1 ), the specific capacitance of CC / AuNPs / PPy@MnO2 is 318 F g -1 , which is nearly 2 times higher than that of CC / PPy electrode; when the current density increases to 40A -1 When the specific capacitance is still maintained at 42F g -1 , indicating that CC / AuNPs / PPy@MnO2 electrode exhibits better capacitive performance at various current densities

[0048] The CV curves of CC / AuNPs / PPy@MnO2 / Lac electrode were tested under air, oxygen-free (N2) and oxygen conditions. The electrolyte was 0.1 M BR buffer (pH 5.0), the scanning range was 0 V to 0.8 V (vs. Ag / AgCl), and the scanning rate was 10 mV·s -1 .

[0049] Test results such as Figure 2 As shown in b, the CC / AuNPs / PPy@MnO2 / Lac electrode exhibits the best electrochemical performance in an oxygen environment.

[0050] 6. EBFC performance evaluation

[0051] The open circuit voltage (OCV) and polarization curve (LSV) of glucose / O2 enzyme biofuel cell (EBFC) were tested using CHI660E electrochemical workstation, and the power density curve was fitted by the polarization curve. The polarization curve and power density fitting curve of CP / AuNPs / PPy@MnO2 electrode and control were tested in 0.1M PBS (pH 7.0) buffer containing 10.0mM glucose.

[0052] Test results such as Figure 6 As shown in ac, the maximum power density of CC / AuNPs / PPy@MnO2 / GOx electrode (0.35 mW cm -2 ) compared with CC / AuNPs / PPy / GOx electrode (0.21 mW·cm -2) was increased by nearly 66.67%; in addition, the OCV of a single glucose / O2 enzyme biofuel cell (EBFC) was measured to be 0.68V, which is higher than most of the glucose / O2 enzyme biofuel cells (EBFC) reported previously.

[0053] The prepared CC / AuNPs / PPy@MnO2 / GOx electrode was stored in PBS (pH 7.0) buffer at 4°C with a concentration of 0.1 M. The polarization curve was measured once a day and the power density curve was fitted to obtain its maximum power density. Taking the power density measured on the first day as the benchmark, its maximum power density could still reach 82% of the initial value after 8 days. Figure 6 d, indicating that the battery has excellent stability.

[0054] In summary, the present invention prepares a novel composite material of carbonized polypyrrole (PPy) and manganese dioxide (MnO2). The material uses a hydrothermal method to grow nano-manganese dioxide on the surface of carbonized polypyrrole, which improves the specific capacitance of the material. The electrode prepared using this material exhibits excellent enzyme capture ability and electron storage capacity. The assembled enzyme biofuel cell (EBFC) exhibits an open circuit voltage (OCV) of up to 0.68V, and the maximum output power density is 0.35mW·cm at 0.49V. -2 , so this material has practical application value.

[0055] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that for those skilled in the art, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0056] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the principles or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for constructing a glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode, comprising: 1) dispersing carbonized polypyrrole powder into potassium permanganate solution and performing hydrothermal reaction to obtain PPy@MnO2 composite material; 2) Printing circuits on flexible plastic films by screen printing, using carbon cloth electrodeposited with NaAuCl4 as the electrode working area, and applying a suspension containing PPy@MnO2 powder droplets on the electrode working area to obtain CC / AuNPs / PPy@MnO2 electrodes; 3) dripping glucose oxidase solution on the working area of ​​the CC / AuNPs / PPy@MnO2 electrode obtained in step 2), and fixing it with chitosan solution after drying to obtain a CC / AuNPs / PPy@MnO2 / GOx electrode; dripping laccase solution on the working area of ​​the CC / AuNPs / PPy@MnO2 electrode obtained in step 2), and fixing it with Nafion solution after drying to obtain a CC / AuNPs / PPy@MnO2 / Lac electrode; 4) Using CC / AuNPs / PPy@MnO2 / GOx electrode as the bioanode, CC / AuNPs / PPy@MnO2 / Lac electrode as the biocathode, and glucose as the fuel, a dual-chamber glucose fuel cell was constructed with the anode chamber and cathode chamber separated by a Nafion membrane.

2. The construction method according to claim 1, characterized in that: In step 1), the carbonized polypyrrole is prepared by a soft template method: first, a FeCl3·6H2O solution is added to a methyl orange solution, and the reaction product is used as an initiator; then, a pyrrole monomer is added under stirring, and polypyrrole is grown using the initiator as a template, followed by filtering, washing, and drying. The dried polypyrrole product is then calcined in a tubular furnace at 800 to 1200° C. under nitrogen protection to obtain carbonized polypyrrole.

3. The construction method according to claim 2, characterized in that: The concentration of the FeCl3·6H2O solution is 40.0 mM to 120.0 mM, the concentration of the methyl orange solution is 4.0 mM to 8.0 mM, the volume ratio of the FeCl3·6H2O solution to the methyl orange solution is 1:1 to 1:10; and the concentration of the pyrrole monomer is 0.02 mM to 0.1 mM.

4. The construction method according to claim 1, characterized in that: In step 1), the concentration of the potassium permanganate solution is 1.0-8.0 mg / mL, the mass ratio of the carbonized polypyrrole to potassium permanganate is 1:10-5:10; and the hydrothermal reaction is carried out at a constant temperature of 80-120° C. for 4-8 hours.

5. The construction method according to claim 1, characterized in that: In step 2), the concentration of the NaAuCl4 solution is 2.0 to 8.0 mM; the electrodeposition is performed at a potential of -1.0 V to -0.2 V for 200 s to 400 s.

6. The construction method according to claim 1, characterized in that: In step 2), the concentration of the suspension containing PPy@MnO2 powder is 4.0-10.0 mg / mL.

7. The construction method according to claim 1, characterized in that: In step 3), the concentration of the glucose oxidase solution is 2.0-8.0 mg / mL; the concentration of the laccase solution is 2.0-8.0 mg / mL.

8. The construction method according to claim 1, characterized in that: In step 3), a ferrocene solution with a concentration of 0.1 M is added as an electron mediator before drop-coating the glucose oxidase solution; and an ABTS solution with a concentration of 10.0 mM is added as an electron mediator before drop-coating the laccase solution.

9. The construction method according to claim 1, characterized in that: In step 4), the CC / AuNPs / PPy@MnO2 / GOx electrode was immersed in a PBS buffer containing 10.0 mM glucose; The CC / AuNPs / PPy@MnO2 / Lac electrode was immersed in 0.1 M BR buffer.

10. A glucose fuel cell based on CC / AuNPs / PPy@MnO2 electrode, obtained by the construction method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for manufacturing amorphous carbon and multi-walled carbon nano-tube composite electrode materials on basis of polypyrrole carbonization

    CN105118997A

  • Biocompatible electrochemical supercapacitor

    CN105324825A